PENGARUH PENGGUNAAN MEDIA KOMIK TERHADAP KEMAMPUAN LITERASI SAINS PESERTA DIDIK - Marlina, Ina; Soepudin, Usep; Ayu Ratna Gumilar, Nyimas (STKIP Subang, 2020)
This study aims to determine the effect of comic media on the scientific literacy skills of students in class IV and to determine the response of students to the use of comic media in classroom learning. The method used in this study is a quasi-experimental method. The research design used was the Nonequivalent Groups Pretest-Posttest Design. The research design consisted of two groups (control class and experimental class), each of which was given a pretest and posttest. The population in this study were students at SD Negeri Cilaja and SD Negeri Ligarmanah, while the sample was taken from two groups, namely class IV SD Negeri Cilaja as the experimental group and class IV SD Negeri Ligarmanah as the control class. Data collection was obtained through description questions in the form of pretest and posttest, as well as statements in the form of a Likert scale questionnaire. The data analysis technique used was quantitative data using Minitab 18.0 software for Windows and Microsoft Excel. In the results of this study, there were changes in the pretest and posttest scores of the experimental class that had increased, at the pretest the mean score of students was 27.75, while in the posttest the average score of students was 40.15. Whereas in the control class the average score of the posttest students was only 34.45. This is reinforced by the results of the N-Gain calculation from the experimental class and the control class which show that the average increase in the experimental class and the control class has a different increase. The experimental class who received learning using comic media had an increase of 38.8% with a moderate increase category. Meanwhile, the control class who received regular learning had an increase of 20.6% with a low increase category. The questionnaire data analysis showed that students gave a positive response to science learning using comic media with an average score of 3.80. In the test results of the difference between the two mean posttest data using the Two Sample T 'test, there is a significant difference between the experimental class and the control class with a significant level of <0.05, it can be concluded that there is an effect of comic media on the scientific literacy abilities of class students. Experiments using comic media have a significantly higher increase compared to the control class with ordinary learning.